Pengembangan Modul Sejarah Lokal Riau Terintegrasi Materi Pembelajaran Sejarah Tingkat SMA - Al Fiqri, Yanuar; Hasibuan, Rizki Ananda (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2023)
This research was motivated by the lack of utilization of local history in historical materials at school. It aims to produce a product in the form of a Riau local history module integrated with high school history material. In this study used the type of R & D research or development by applying the 4D model (Define, Design, Development and Dissemination). The results of the research are in the form of teaching modules that contain 6 local history materials in Riau, consisting of: The life of the Akit tribe, Muara Takus Temple, Siak Palace and Kingdom, History of the establishment of Pekanbaru City by Mahrum Pekan, Construction of the Muaro Sijunjung-Pekanbaru railroad line during the Japanese period and the role of Mahmud Marzuki in reporting news of independence in Kampar. The module was then assessed by material, design and instrument validators to determine whether the developed module is suitable for use in schools. The results of the material validation received a value of 95% with a very feasible category, module design validation with a result of 92.8% very feasible criteria and question instrument validation with a value of 90% very feasible criteria.